Effects of pesticides on eggs of Chrysoperla externa (Neuroptera: Chrysopidae) and consequences on subsequent development - SILVA, ROGÉRIO ANTÔNIO; ANDRADE-CARVALHO, GERARDO; FREIRE-CARVALHO, CÉSAR; BASTOS-SILVA, DIEGO (Revista Colombiana de Entomología, 2012)
The effects of six pesticides applied to the coffee crop on eggs and their consequences on the subsequent de- velopmental stages of Chrysoperla externa (Neuroptera: Chrysopidae) were evaluated under laboratory conditions. The pesticides and water (control) were sprayed on eggs using a Potter´s tower. After spraying, forty eggs per treatment were individualized in glass tubes and maintained in a climatic chamber, in order to evaluate immature development of this predator. The treatments showed significant differences for egg viability and survival of first-instar larvae. Chlorpyrifos, sulphur and copper oxichlorate reduced the treated egg viability, whereas both sulphur and betacyfluthrin reduced the survival of first-instar larvae. Endosulphan and azociclotin reduced the daily oviposition of this green lacewing species. The harmless products (Class 1, E < 30%), can be recommended for use in integrated pest management programs in coffee crops, in order to preserve this predator.